Modular in-service training for reading teachers - Ferrer, Imelda Caravaca- (2005)
It was hypothesized in this study that exposure to the in-service training modules consisting of input in instructional strategies would increase the teachers' know-how, change his/her perception of reading and eventually rebound to improvement of their pupils on reading skills. Findings showed that the modular instruction increased the knowledge of teachers because the learning package targeted their perceived pedagogical needs.